An exploration of the reactivity of singlet oxygen with biomolecular constituents. Issue 73 (18th August 2016) - Marchetti, Barbara; Karsili, Tolga N. V.
Abstract : The complex reactivity of singlet O2 with a given biomolecule is revealed by multi-reference electronic structure theory. Abstract : The thermal reaction between biomolecules and singlet oxygen ( 1 O2 ) is important for rendering the genetic material within toxic cells inactive. Here we present results obtained from state-of-the-art multi-reference computational methods that reveal the mechanistic details of the reaction between 1 O2 and two exemplary biomolecular systems: guanine (Gua) and histidine (His). The results highlight the splitting of the doubly degenerate 1 Δg state of O2 upon complexation and the essentially barrierless potential energy profile of the thermally allowed cycloaddition reaction when the O2 molecule is in its lower energy 1 Δg state.